An Andalusian Bridge over the Llobregat River - Hernández Cardona, Ángel Manuel; Navarro Herrerías, Eleuterio (Anaquel de Estudios Árabes, 2007)
Remains of an Andalusian bridge over the Llobregat river are found in el Cairat, a Catalonian town near Montserrat. It was 60 metres long and 2.5 metres wide and had five archs. It has proved to be an Andalusian bridge because of its construction characteristics: mainly basket-handle archs and building stones arranged by alternating courses of headers (short side of the brick facing out) with courses of stretchers (long side of the brick facing out). It can’t be a Roman bridge because of its width and other features, nor a bridge of Romanesque or Gothic styles because of the shape of the archs and the absence of opus vittatum. Early Middle Ages roads and fortifications (some Andalusian) and pre-Romanesque churches (some Visigothic or Mozarabic) are analyzed. Between the interesting place-names of Arabic origin, a mirror of signals, a mill, a waterwheel, a fishery, and a pass dedicated to the emir are discussed in this study.